Crop wild relatives in the South African development community - Dulloo, Mohammad Ehsan; Maxted, Nigel; Shave, Justify; Pungulani, Lawrent; Hamisy, William; Munkombwe, Graybill; Magos Brehm, Joana; Bissessur, Prishnee (Bioversity International and the International Center for Tropical Agriculture, 2021)
The countries of the South African Development Community (SADC) are facing unprecedented challenges related to food security, climate change and poverty reduction. The conservation and sustainable use of crop wild relatives (CWR), which is worth an estimated US$120 billion globally, should be an urgent priority for the region. This policy brief outlines the current status of the SADC’s CWR and provides an outline for policymakers to form a regional network to better protect CWR to improve food security, livelihoods, and the conservation of biodiversity.